Assessment instruments for pressure injury healing: integrative review (Research, Society and Development, 2020)
Objective: To identify instruments that supports the assessment of the healing of pressure injuries. Methodology: This is an integrative review conducted on the following data sources: Cumulative Indez to Nursing and Allied Health Literature (CINAHL), Scopus, Science Direct, Web of Science, Cochrane Library, Medline, Latin American & Caribbean Health Sciences Literature (LILACS), US National Library of Medicine (PubMed Central) and Biblioteca Virtual em Saúde (BVS). The following were included: Articles that answer the research question, available in full, in Portuguese, English or Spanish. Excluded: Repeated articles, literature reviews and expert opinions. Results: 279 studies were collected between 2009 and May 2020, of these 16 were analyzed. Among the seven instruments identified, the Pressure Ulcer Scale for Healing was the most frequent (36.6%). The most prevalent characteristics of the instruments were lesion size, type of tissue and amount of exudate. Regarding psychometric properties, the BWAT scale was translated and adapted to Brazilian culture, DESIGN-R had predictive validity, PUSH obtained internal and external responsiveness and HPR performed preliminary validity. None of the instruments have clinical validity. Conclusion: The results obtained revealed that the theme is little explored, especially in Portuguese-speaking countries. The lack of uniformity between the healing assessment instruments makes it difficult to standardize the parameters necessary for the assessment, to register the procedures and to compare results between researches on the same theme.